2021
DOI: 10.3390/su132413944
|View full text |Cite
|
Sign up to set email alerts
|

Why People Settle in Shrinking Communities: A Unified Framework of Psychological, Environmental, and Cognitive Factors

Abstract: The interpretation of settlement behavior in shrinking areas can provide insights into sustainability strategies in shrinking communities. However, the choice to settle in areas undergoing shrinkage is hard to interpret when considering residents as rational decisionmakers. To attain a deeper understanding of this decision-making process, a framework of residential decision making (RDM) considering a subjective environmental evaluation dimension, psychological dimension, and cognitive dimension is proposed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Siyi An has studied settlement behaviour in shrinking areas, establishing an RMD framework through subjective, environmental evaluation dimensions, mental dimensions, and cognitive dimensions, and conducting questionnaires in different communities in Japan. The findings were that residents of suburban communities tend to consider overall satisfaction with their location when considering settlement, while residents of mountainous communities place more emphasis on emotional satisfaction factors, with the results suggesting that area design that enriches residential experience and neighbourhood communication is important in promoting population settlement [23].…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Siyi An has studied settlement behaviour in shrinking areas, establishing an RMD framework through subjective, environmental evaluation dimensions, mental dimensions, and cognitive dimensions, and conducting questionnaires in different communities in Japan. The findings were that residents of suburban communities tend to consider overall satisfaction with their location when considering settlement, while residents of mountainous communities place more emphasis on emotional satisfaction factors, with the results suggesting that area design that enriches residential experience and neighbourhood communication is important in promoting population settlement [23].…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Some studies have established a two-way link between attachment to place and residential satisfaction. For example, a research conducted by An et al (2021) found a strong relationship between attachment to place and residential satisfaction in suburban and mountainous communities. Despite numerous measurements of livability and investigations into its relationship with place attachment, several gaps in the research background remain.…”
Section: Livability and Attachment To Placementioning
confidence: 99%